(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The research is aimed at identifying trends in the adaptation of the institutional environment to modern market conditions. The goal was achieved by solving the problem of identifying changes in the organization’s institutional environment related to innovation, in particular, digital transformation and the introduction of lean production. The modernization of formal institutions contributes to the formation of informal norms based on the adoption of "digital" standards of thinking and the philosophy of lean production.